Toward a New Understanding of Nineteenth-Century Cost Accounting. - Johnson, H. Thomas (The Accounting Review, 1981)
ABSTRACT: While accounting historians agree that cost accounting is a consequence of the industrial revolution, they have not thoroughly explained the economic consequence of the industrial revolution which prompted manufacturing firms to develop actual cost accounting techniques in the nineteenth century. This paper presents an explanation for the rise of nineteenth-century cost accounting which supplements the traditional view that increased use of fixed capital and the resultant need to account for costs of long-lived assets prompted industrial accountants to graft cost accounts onto the double-entry system. The study concludes that not only changes in the temporal structure of their costs, but also changes in the way they organized economic activity, explain the conditions which prompted manufacturers to develop cost accounting procedures for gathering financial information needed by managers.